A review of climate change and the implementation of marine biodiversity legislation in the United Kingdom. Issue 3 (28th January 2016) - Frost, Matthew; Bayliss‐Brown, Georgia; Buckley, Paul; Cox, Martyn; Dye, Stephen R.; Sanderson, William G.; Stoker, Bethany; Withers Harvey, Narumon
Abstract: Marine legislation, the key means by which the conservation of marine biodiversity is achieved, has been developing since the 1960s. In recent decades, an increasing focus on 'holistic' policy development is evident, compared with earlier 'piecemeal' sectoral approaches. Important marine legislative tools being used in the United Kingdom, and internationally, include the designation of marine protected areas and the Marine Strategy Framework Directive (MSFD) with its aim of meeting 'Good Environmental Status' (GES) for European seas by 2020. There is growing evidence of climate change impacts on marine biodiversity, which may compromise the effectiveness of any legislation intended to promote sustainable marine resource management. A review of key marine biodiversity legislation relevant to the UK shows climate change was not considered in the drafting of much early legislation. Despite the huge increase in knowledge of climate change impacts in recent decades, legislation is still limited in how it takes these impacts into account. There is scope, however, to account for climate change in implementing much of the legislation through (a) existing references to environmental variability; (b) review cycles; and (c) secondary legislation and complementary policy development. For legislation relating to marine protected areas (e.g. the EC Habitats and Birds Directives), climate change has generally not been considered in the site‐designation process, or for ongoing management, with the exception of the Marine (Scotland) Act. Given that changing environmental conditions (e.g. rising temperatures and ocean acidification) directly affect the habitats and species that sites are designated for, how this legislation is used to protect marine biodiversity in a changing climate requires further consideration. Accounting for climate change impacts on marine biodiversity in the development and implementation of legislation is vital to enable timely, adaptive management responses. Marine modelling can play an important role in informing management decisions. Copyright © 2016 John Wiley & Sons, Ltd.